Oxidation kinetics of nitrogen doped TiO2-delta thin films - Shi, Jianmin; Lee, Doh-Kwon; Yoo, Han-Ill; Janek, Juergen; Becker, Klaus-Dieter (ROYAL SOC CHEMISTRY, 2012)
The oxidation kinetics of nitrogen doped, oxygen deficient titanium dioxide thin films has been studied in atmospheres of pure oxygen or nitrogen at 500 degrees C, 550 degrees C, and 600 degrees C, respectively, by means of in situ optical spectroscopy. The thin films show high electronic absorbance in the visible and NIR region, accompanied by a red shift of the absorption edge of about 0.4 eV, e.g., from about 2.9 to 2.5 eV at 600 degrees C. The time dependent decrease of absorbance due to oxidation is found to follow a parabolic rate law. An activation energy of about 1.96 eV can be obtained from the temperature dependence of the parabolic oxidation rate constant. In the framework of a microscopic oxidation model, this energy barrier is attributed to the diffusion of titanium interstitials in the re-oxidized part of the thin films as a rate-determining process. In addition, an attempt is made to evaluate the kinetics of nitrogen release from the time dependent blue shift of the absorption edge during re-oxidation.
Keywords: VISIBLE-LIGHT PHOTOCATALYSIS; OPTICAL IN-SITU; ELECTRICAL-CONDUCTIVITY; OXYGEN NONSTOICHIOMETRY; EQUILIBRATION KINETICS; CHEMICAL DIFFUSION; DEFECT CHEMISTRY; ANATASE TIO2; BAND-GAP; SURFACE